Effect of air pollution on asthma - Zhou, Xiaoying; Sampath, Vanitha; Nadeau, Kari C (Annals of allergy, asthma, & immunology, 2024)
Asthma is a chronic inflammatory airway disease characterized by respiratory symptoms, variable airflow obstruction, bronchial hyperresponsiveness, and airway inflammation. Exposure to air pollution has been linked to an increased risk of asthma development and exacerbation. This review aims to comprehensively summarize recent data on the impact of air pollution on asthma development and exacerbation. Specifically, we reviewed the effects of air pollution on the pathogenic pathways of asthma, including type 2 and non-type 2 inflammatory responses, and airway epithelial barrier dysfunction. Air pollution promotes the release of epithelial cytokines, driving T 2 responses, and induces oxidative stress and the production of proinflammatory cytokines. The enhanced type 2 inflammation, furthered by air pollution-induced dysfunction of the airway epithelial barrier, may be associated with the exacerbation of asthma. Disruption of the T 17/regulatory T cell balance by air pollutants is also related to asthma exacerbation. As the effects of air pollution exposure may accumulate over time, with potentially stronger impacts in the development of asthma during certain sensitive life periods, we also reviewed the effects of air pollution on asthma across the lifespan. Future research is needed to better characterize the sensitive period contributing to the development of air pollution-induced asthma and to map air pollution-associated epigenetic biomarkers contributing to the epigenetic ages onto asthma-related genes.